Abdul Halim Hasan and His Methodological Approach in Tafsir al-Quran al-Karim (Abdul Halim Hasan dan Metodologinya dalam Tafsir al-Quran al-Karim) - Ahmad, Nadzrah (Journal of Islam in Asia (E-ISSN 2289-8077), 2017)
Abstract Abdul Halim Hasan was a Malay exegetical writer of Indonesian origin. His work on Qur’anic exegesis or tafsir, transcended geographical boundaries and reached audiences around the Malay regions, especially Malaysia. The academic value of this particular tafsir is undeniably outstanding as an early twentieth century exegetical writing. This paper highlights Abdul Halim Hasan and his academic measures in the writing of Tafsir al-Quran al-Karim. Emphasis was given towards his biography and methodological contribution in tafsir. This qualitative study utilized deductive and inductive method to examine and discuss his tafsir as well as methodology. The result indicated that Abdul Halim Hasan implemented specific methodology in his tafsir, benefitting from his reference of the past scholars in this field. Keywords: Tafsir methodology, Tafsir al-Quran al-Karim, Abdul Halim Hasan, Tiga Serangkai, Indonesian exegesis, Malay Archipelago. Abstrak Abdul Halim Hasan merupakan ulama tafsir Melayu yang berasal dari Indonesia. Pengaruh tafsirnya melangkaui sempadan ke seluruh Nusantara terutamanya Malaysia. Nilai akademik bagi karya tafsirnya ini tidak dapat disangkal lagi sebagai sebuah tafsir berpengaruh awal kurun ke dua puluh. Artikel ini bertujuan untuk melihat latarbelakang bagi pengarang tafsir ini, Haji Abdul Halim Hassan, dan karya akademiknya, Tafsir al-Quran al-Karim. Fokus utama akan diberikan terhadap biografi penulis sumbangannya dari sudut metodologi dalam penafsiran al-Quran. Kajian ini adalah suatu kajian kualitatif yang akan menggunapakai kaedah deduksi dan induksi, bagi menkaji dan menyususun metodologi yang dipraktik oleh beliau dalam penulisan tafsirnya. Kajian mendapati beliau menggunakan kaedah khusus didalam penafsirannya yang diambil dari kefahamannya keatas penulisan tafsir oleh ulama-ulama terdahulunya, Kata Kunci: Metodologi Tafsir, Tafsir Al-Quran Al-Karim, Abdul Halim Hasan, Tiga Serangkai, Ulama Tafsir Indonesian, Kepulauan Melayu Nusantara.